MUSIC MANAGEMENT- NEW OPPORTUNITIES NEW CHALLENGES - Saxena, Anjana (International Journal of Research -GRANTHAALAYAH, 2015)
The transition to digital is changing the music industry. As technology has advanced over recent years, the music industry has consequently undergone a drastic change in the way it operates. This industry-wide shift has its pros and its cons: On one hand, the internet serves as an incredible platform on which anyone can exhibit their talent and potentially build a fan base. On the other hand, the presence of millions of people attempting to do so make it more and more difficult for any one person to stand out, and the reality of file sharing and illegal downloading makes the financial aspect of music much more complex. Regardless of one`s opinion about the road that the music industry has traveled down, a music manager must be flexible enough to keep up with the changes that the industry undergoes. The meaning and role of a “manager” has changed drastically over the last decade as the traditional business model has given way to the “new” music business Traditionally a manager managed an artist’s efforts to get signed to a label and once signed, he/she managed the relationship between the artist and the label. But given the state of labels today the unsigned artist must assume that he/she will never be signed and build a career accordingly. A traditional manager is often unable and ill – equipped to successfully manage and develop an artist’s career in the new environment.